Datu Jatmiko PERAN STAKEHOLDER SEKOLAH DALAM MENGATASI BERBAGAI MACAM KEKERASAN DI KALANGAN SISWA - Jatmiko, Datu (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2017)
ABSTRACT This article aims to determine the role of all school stakeholders in the range of violence experienced by students in the school. Various kinds of violence experienced by students in schools today can not be separated from their social environment including the school environment itself. Violence in the form of verbal abuse, for example bullying, slander, insult, berate and curse in the real world that can lead to psychological violence. Then the virtual violence such as insulting, insulting and cursing in the virtual world or social media up to physical violence such as beatings, sexual abuse, penamparan and others. The role of school stakeholders include the role of the principal as a leader and manager of the school then the teachers as mentors, tutors, teachers and educators to school employees and school friend or peer itself as the outpouring of the heart. That role from the role of prevention or preventive then the role of prevention or repressive efforts hngga entire school community participatory role in preventing and combating violence among students. Key words: School stakeholders, Violence, Students.